Novosti pri zdravljenju povišanega holesterola - Štrukelj, Borut (Farmacevtski vestnik, 2022)
Low-density lipoprotein cholesterol (LDL-cholesterol) is one of the most important causal factors associated with cardiovascular diseases. Among established therapies with statins and ezetimib, the last decade has been focused in the development and use of PCSK-9 inhibitors. The PCSK-9 protein binds to an LDL receptor and accelerates its degradation and increases levels of LDL-cholesterol. Two human monoclonal antibodies, evolocumab and alirocumab, are used as PCSK-9 inhibitors, while an even more revolutionary approach has been reached by a small two-stranded interfering RNA (siRNA), known as inclisiran. Inclisiran binds to mRNA for PCSK-9 and triggers its degradation, which results in increased uptake and metabolism of LDL-cholesterol in hepatocytes, and a decrease of LDL-cholesterol plasma levels.
Keywords: Holesterol; inklisiran; LDL-holesterol; monoklonska protitelesa; zaviralci PCSK-9